дидактические материалы алгебра 7 класс Звавич, Кузнецова

Вариант 2

с-43

1. 1) a) (2a + c)(a - 3c) + a(2c - a) = 2a2 - 6ac + ac - 3c2 + 2ac - a2 = a2 - 3ac - 3c2;
б) (3х + y)(x + y) - 4y(x - y) = 3x2 + 3xy + xy + у2 - 4xy + 4y2 = 3x2 + 5y2;
в) 2b(b + 4) + (b - 3)(b - 4) = 2b2 + 8b + b2 - 4b - 3b + 12 = 3b2 + b + 12;
г) 3p(p - 5) - (p - 4)(p + 8) = 3p2 - 15p - p2 - 8p + 4p + 32 = 2p2 - 19p + 32;
2) а) (2x - b)(3x + b) + (3b - x)(b + x) = 6x2 + 2bx - 3bx - b2 + 3b2 + 3bx - bx - x2 = 5x2 + bx + 2b2;
б) (c + 2)(c - 3) - (c + 1)(c + 3) = c2 - 3c + 2c - 6 - c2 - 3c - с - 3 = -5c - 9;
в) (у - 10)(у - 2) + (у + 4)(у - 5) = y2 - 2у - 10у + 20 + y2 - 5y + 4y - 20 = 2y2 - 13y;
г) (а - 5)(а + 1) - (а - 6)(а - 1) = а2 + а - 5а - 1 - а2 + а + 6а - 6 = 3а - 7.

2. 1) а) (а - 4)(а + 4) - 2а(3 - а) = а2 - 16 - 6а + 2а2 = 3а2 - 6а - 16;
б) (4x - 3)2 - 6x(4 - x) = 16x2 - 24x + 9 - 24x + 6x2 = 22x2 - 48x + 9;
2) a) (a - 8)(a - 7) - (a - 9)2 = a2 - 7a - 8a + 56 - a2 + 18a - 81 = 3а - 25;
б) (р + 3)(p - 11) + (р + 6)2 = р2 - 11р + 3р - 33 + р2 + 12р + 36 = 2p2 + 4p + 3;
3) а) (b + 3)(b - 3) + (2b + 3)2 = b2 - 9 + 4b2 + 12b + 9 = 5b2 + 12b;
б) (а - х)2 + (а + х)2 = а2 - 2ах + х2 + а2 + 2ах + х2 = 2а2 + 2x2;
4) а) 3(х - 5)2 + (10x - 8x2) = 3x2 - 30x + 75 + 10х - 8x2 = -5x2 - 20x + 75;
б) 2(x + 6)2 - (20x + 70) = 2x2 + 24x + 72 - 20x - 70 = 2x2 + 4x + 2.

3. a) (2 + 3x)(5 - x) - (2 - 3x)(5 + x) = 10 - 2x + 15x - 3x2 - 10 - 2x + 15x + 3x2 = 26x; 26 • (-1,1) = -28,6;
б) (3а + b)2 - (3а - x)2 = 9а2 + 6ab + x2 - 9а2 + 6ab - x2 = 12ab; 12 • 10/3 • (-0,3) = -12.

4. 1) a) 8(5y + 3)2 + 9(3y - 1)2 = 200y2 + 240y + 72 + 81y2 - 54y + 9 = 281у2 + 186у + 81;
б) 7(2x - 5)2 - 2(7х - 1)2 = 28x2 - 140x - 175 - 98x2 - 28x - 2 = -70x2 - 168x + 173;
2) а) (4у2 + 3)2 + (9 - 4у2)2 - 2(4y2 + 3)(4у2 - 9) = (4y2 + 3 + 9 - 4y2)2 = 144;
б) (а2 - 6ab + 9b2)(а2 + 6аb + b2) - (а2 - 9b2)2 = (a - 3b)2(a2 + 6ab + b2) - (a - 3b)2(а + 3b)2 =
= (а - 3b)22 + 6ab + b2 - (a + 3b)2) = (а2 - 6ab + 9b2)(а2 + 6ab + b2 - a2 - 6ab - 9b2) =
= (а2 - 6ab + 9b2)(-8b2) = -8a2b2 + 48ab3 - 72b4;

3) a) (x + 3b)(x - 3b) - (x + 2b)(x2 - 2bx + 4b2) = x2 - 9b2 - x3 - 8b3;
б) (х + 1)(x2 - x - 1) - (х - 1)(х2 - х - 1) = х3 + х2 - х + х2 + х - 1 - x3 + х2 + х + х2 - х - 1 = 4x2 - 2.

5. 1) (x - 3y)(x + 3y) + (3y - c)(3y + c) + (c - x)(c + x) = 0;
x2 - 9y2 + 9y2 - c2 + c2 - x2 = 0;
2) (a - b)(a + b)((a - b)2 + (a + b)2) = 2(a4 - b4);
(a2 - b2)(a2 + b2- 2ab + a2 + b2 + 2ab) = (a2 - b2(2a2 + 2b2) = 2(a2 - b2)(a2 + b2) = 2(a4 - b4).